ANALYSIS OF CUSTOMER ENGAGEMENT BEHAVIOR FOR SMALL AND MEDIUM SOUVENIR ENTERPRISES IN MANADO - Wijayati, Saputri Dwi; Massie, James D.D; Tumewu, Ferdinand J. (Universitas Sam Ratulangi, 2018)
Abstract: Tourism sector has increasingly become very dynamic and significant sector consists of many small and medium souvenir enterprises that tried to be successful in competitive market. Engagement marketing is powerful marketing strategy since customer can co-create the value and influence customer in broader population. This research aims to examine the implementation of engagement marketing strategy and analysis the costumer engagement behavior toward the engagement marketing strategy. The present research implies a qualitative study conducted using interview with the owner store, head store, senior employee of the store and the customer of the small and medium souvenir enterprises. The result of this research, brand awareness become the main purpose while implement this strategy, there is still gap between offline and online in implementing engagement marketing strategy, also still lack of receive feedback from the customer. Most of customer will voluntarly suggest customer in broader population. Souvenir enterprises need to more persistently boost their online marketing process like in keeping connected with customers online for make sure that customer have access for two way communication , also should enhance the customer feedback by giving a reward for the best suggestion and correlate both offline and online engagement marketing as well. Â Keyword: engagement marketing, online engagement marketing, offline engagement marketing, customer engagement behavior, costumer purchasing behavior, customer influencer value, customer knowledge value.